Gift Exchange in a Multi-worker Firm - Sandra Maximiano; Randolph Sloof; Joep Sonnemans (Tinbergen Institute, 2004)
One of the main findings of a large body of gift exchange experiments is that in an incomplete contracts environment workers on average do not shirk and usually provide more than the minimum enforceable effort level. In general, 40 to 60 percent of the workers reward higher wages with higher effort. These results are observed for simple one-employer - one-worker relationships. In this paper we investigate whether they generalize to the more realistic situation in which the employer employs several workers. We compare a bilateral gift exchange game with a treatment in which each employer has four workers. We find that effort levels in the latter treatment are only marginally lower. Gift exchange thus appears to be robust to increases in the size of the workforce and intention-based reciprocity rather than social preferences seems to be the main driving force behind gift exchange.
Keywords: J41; C91; 330; gift exchange; multiple workers; reciprocity; experiments; Vergütungssystem; Geschenk; Leistungsanreiz; Anreizvertrag; Spieltheorie; Test; Theorie